The Students’ Ability in Using Subject-Verb Agreement in Grade XI IPS 1 of SMA Ar-Rahmah Malang - Karlina Karadila Yustisia (Universitas Merdeka Malang, 2017)
The aims of this study is to describe the approach used by the teacher in teaching subject-verb agreement, the students’ ability in using subject-verb agreement and the error occur made by the students in using subject-verb agreement. The research found that the teacher was used deductive approach and grammar practice in raising the students’ consciousness on Students’ Ability in Using Subject-Verb Agreement. The student’ ability in using subject-verb agreement categorized into poor was 58% (15 students from 27 population of the students in the class). This study also found that there were four sources of errors due to the errors. In conclusion, the highest error made by students dealing with subject-verb agreement were on inter language transfer, negative transfer, overgeneralization and simplification.